Pijat Bayi Terapi Komplementer untuk Optimalkan Tumbuh Kembang Anak - Dessy Abdullah; Ade Teti Vani; Mutiara Anissa; Nadia Purnama Dewi; Anita Darmayanti (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
The development of a child is very important for parents. Every parent wants their child to grow up well and be a strong and good quality child. One of the efforts that parents can do from an early age is to stimulate with the baby massage method. Massage therapy is one of the complementary therapies that can stimulate tactile-kinesthetic stimulation. Massage therapy given since infancy can increase the stimulation of receptors on the skin, affect brain cells, increase interaction between mother and child, and increase body weight so that children's growth becomes optimal. This community service activity aims to increase community knowledge at the Sinar Gunung VI Posyandu, about baby massage and how to do it, so that babies can grow and develop properly. The method used is lecturing and practicing as well as distributing leaflets on how to do a baby massage that will optimize the growth and develop optimally of children. This activity was attended by 18 mothers who have babies. The results of this activity were increased knowledge and skills of mothers who came to Posyandu Sinar Gunung VI who had babies. The conclusion is that there is an increase in the knowledge and skills of mothers who have infants and higher confidence in practicing complementary therapy for infant massage therapy with mentoring and coaching to optimize the growth and develop optimally of infants.